Adhesive for UTG protective film, preparation method and UTG protective film
By combining adhesives without silicon and fluorine with ammonium salts and multi-wall carbon nanotubes, the antistatic properties and peeling force of the UTG protective film are solved, and the residual glue and ghost-free effect is achieved, satisfying the non-existent effect The sustainable development needs of fluorine materials.
Patent Information
- Application Number
- CN202411299602.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The existing UTG protective film lacks antistatic properties and contains fluorine additives, which cannot meet the sustainable development needs of fluorine-free materials. At the same time, the peeling force is high and it is prone to residual glue and ghost problems.
Adhesives synthesized by polyester polyols, diisocyanates, chain extenders, antistatic agents and closed isocyanates in solvent and catalyst environments, combining ammonium salts with multi-wall carbon nanotubes , a UTG protective film with good antistatic properties is formed, and antistatic agents and carbon nanotubes are introduced into the polymer chain through specific chemical reactions to enhance the stability of the adhesive.
The prepared UTG protective film has excellent antistatic properties and optical properties. It is closely bonded to the UTG surface after high temperature and high humidity test. There is no residual glue or ghost after peeling off. The resistance value is low, which meets customer requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive for a UTG protective film, a preparation method and the UTG protective film, and belongs to the technical field of optical protective films. Background Art
[0002] Foldable devices are increasingly popular due to their excellent portability and unique design, and are widely used in foldable mobile phones, car-mounted, smart wearable devices, electronic devices and other fields. Ultra-thin glass (UTG) is a special glass material used in foldable screen mobile phones. It has the advantages of lightness, high hardness, scratch resistance, good touch, and high temperature resistance. The thickness is usually between 0.1mm and 1.2mm. UTG with a thickness of less than 0.2mm has the characteristic of foldability. Protective film is used in both UTG process and shipment protection. In October 2020, the European Commission issued the "Chemical Sustainable Development Strategy". The new strategy aims to better protect citizens and the environment, promote safe and sustainable chemical innovation, and achieve the goal of non-toxic environment and zero pollution. The gradual elimination of perfluorinated (polyfluorinated) organic compounds (PFAS) within the EU is a key measure in the sustainable development strategy of chemicals. Optical protective films are also moving towards fluorine-free materials.
[0003] Chinese patent CN202211270924 discloses a low surface energy change cover glass protective film and a preparation method. The protective film includes a PE substrate layer and an acrylic pressure-sensitive adhesive layer, which effectively improves the problem of surface energy drop after the protective film is attached to the cover glass, so that the surface energy of the glass cover is stabilized at above 36 dynes, meeting the subsequent bonding adhesion of the ink surface, and solving the problem that the surface energy of the ink area and the window area of the glass frame drops below 34 dynes after the cover glass is attached. However, the protective film does not have antistatic properties and has a high peeling force (5g / 25mm-10g / 25mm), and cannot be used for UTG protective film. Chinese patent CN202311724464.2 discloses a cover glass protective film and a preparation method thereof. The prepared cover glass protective film is treated with antistatic treatment on one side of the PET substrate layer, and an antistatic polyurethane modified pressure-sensitive adhesive layer is formed on the other side, and a PET release film layer is formed on the surface of the pressure-sensitive adhesive layer, so as to prepare a film-resistant and adhesive-resistant double-resistant protective film with antistatic function, and has extremely low and stable film tearing voltage performance, high electronic equipment process yield, and can meet customers' requirements for a film tearing voltage of less than 500V. However, the protective film uses fluorine-containing additives and cannot be applied to UTG protective films. Summary of the invention
[0004] In order to overcome the drawbacks of the prior art, the present invention provides an adhesive for a UTG protective film, a preparation method and a UTG protective film. The adhesive does not contain silicon and fluorine, is used as a UTG protective film, and has antistatic properties. After a high temperature and high humidity test for 500 hours, the protective film is tightly attached to the UTG surface without bubble bulging, and there is no residual glue, ghosting and other drawbacks after the protective film is torn off.
[0005] The technical solution adopted by the present invention to solve the technical problem is: An adhesive for a UTG protective film, the adhesive is a polyester polyol, a diisocyanate, a chain extender, an antistatic agent and a blocked isocyanate, a polymer free of silicon and fluorine is obtained in a solvent and catalyst environment, and includes the following substances in parts by weight: Polyester polyol 10-20 parts 8-12 parts of diisocyanate Chain extender 1-3 parts Solvent 20-40 parts Antistatic agent 0.5-2 parts Catalyst 0.3-0.6 parts 5-10 parts of blocked isocyanate.
[0006] In the adhesive for the UTG protective film, the antistatic agent is a mixture of ammonium salt and multi-walled carbon nanotubes, and the weight ratio of the ammonium salt to the multi-walled carbon nanotubes is 1:1-4:1.
[0007] The adhesive for the UTG protective film, the ammonium salt is 86443-82-5 cationic quaternary ammonium salt surfactant; the multi-walled carbon nanotubes are two kinds of multi-walled carbon nanotubes with a diameter of 20nm and a length of 1μm and multi-walled carbon nanotubes with a diameter of 10nm and a length of 5μm in any weight ratio.
[0008] In the above-mentioned adhesive for UTG protective film, the polyester polyol is one of polyethylene adipate glycol diol and polycarbonate polyol or two of them in any weight ratio; the diisocyanate is one of 1,6-hexamethylene diisocyanate and trimethylhexamethylene diisocyanate or two of them in any weight ratio.
[0009] In the adhesive for the UTG protective film, the chain extender is one of 4,4'-methylenebis(2-methyl-6-ethylaniline) and 2,4-diamino-3,5-diethyltoluene or two of them in any weight ratio.
[0010] In the adhesive for the UTG protective film, the solvent is one of ethyl acetate and butyl acetate or two of them in any weight ratio; the catalyst is one of dibutyltin dilaurate and stannous octoate or two of them in any weight ratio.
[0011] A method for preparing an adhesive for a UTG protective film, the preparation method comprising the following steps: a. Add the proportion of polyester polyol, diisocyanate, chain extender and solvent into the reactor and react at 40℃-50℃ for 20min-40min; b. Add a proportion of catalyst and heat to 70-90°C for 1-3 hours; c. Add a proportion of antistatic agent, keep the reaction at 70℃-90℃ for 1h-2h, cool to 40℃-50℃, add a proportion of blocked isocyanate, and obtain the adhesive for UTG protective film.
[0012] A UTG protective film is prepared by coating the adhesive for the UTG protective film on the surface of a polyester film, and laminating a release film on the adhesive layer.
[0013] The above-mentioned UTG protective film, the polyester film is a 50μm optical grade polyester film, and the thickness of the adhesive layer is 8μm-12μm The beneficial effects of the present invention are: 1. The present invention uses ammonium salt antistatic agents and multi-walled carbon nanotubes in combination. Carbon nanotubes can provide the protective film with excellent antistatic properties, and ammonium salt antistatic agents are beneficial to improving the excellent optical properties of the protective film. The protective film prepared by the combination of the two has excellent antistatic and optical properties.
[0014] 2. The present invention uses chemical reaction to remove the amino group (-NH 2 ) reacts with the isocyanate group (-NCO) to introduce the ammonium salt into the polymer chain, effectively preventing the antistatic agent from precipitating.
[0015] 3. The present invention selects multi-walled carbon nanotubes through chemical reaction. The surface of multi-walled carbon nanotubes contains carboxyl groups (-COOH) which can react with isocyanate groups (-NCO) to introduce carbon nanotubes into polymer chains, effectively preventing the precipitation of antistatic agents and improving the stability of the adhesive layer of the protective film.
[0016] 4. The present invention uses polyester polyols, and the prepared adhesive contains more ester groups, amino groups and other machine-type groups, which improves the cohesive strength of the adhesive, and the prepared protective film has no residual adhesive after being attached to UTG.
[0017] 5. The adhesive for the UTG protective film prepared by the present invention does not require a curing agent to be added during use and can be directly coated on a machine, thereby reducing the adhesive preparation process.
[0018] 6. The resistance of the protective film layer is 1×10 10Ω or less, when the adhesive layer of the protective film is attached to the UTG surface, after 500h of high temperature and high humidity test, the protective film is tightly attached to the UTG surface without bubbles, and there is no residual glue, ghosting and other defects after removing the protective film. DETAILED DESCRIPTION
[0019] The present invention provides an adhesive for a UTG protective film, a preparation method and a UTG protective film. The prepared UTG protective film has antistatic properties and does not contain silicon and fluorine. The present invention adds an ammonium salt antistatic agent and multi-walled carbon nanometers to the adhesive to give the adhesive antistatic properties, form a conductive channel in the adhesive, and eliminate static electricity faster. The two antistatic agents are used in combination to achieve a better antistatic effect.
[0020] In order to obtain an adhesive with the desired performance, the present invention further restricts the components of the adhesive, in detail: the adhesive includes the following substances in parts by weight: 10-20 parts of polyester polyol, 8-12 parts of diisocyanate, 1-3 parts of chain extender, 20-40 parts of solvent, 0.5-2 parts of antistatic agent, 0.3-0.6 parts of catalyst and 5-10 parts of blocked isocyanate.
[0021] Furthermore, in order to improve the optical properties and antistatic properties of the protective film, the antistatic agent is a combination of ammonium salt and multi-walled carbon nanotubes; considering the two indicators of resistance value and compatibility, the weight ratio of the ammonium salt to the multi-walled carbon nanotubes is 1:1-4:1. If too much multi-walled carbon nanotubes are added, the antistatic agent is likely to precipitate and affect the optical properties of the protective film.
[0022] Furthermore, in order to improve the antistatic performance of the protective film, the ammonium salt is a 86443-82-5 cationic quaternary ammonium salt surfactant; the multi-walled carbon nanotubes are two kinds of multi-walled carbon nanotubes with a diameter of 20 nm and a length of 1 μm and multi-walled carbon nanotubes with a diameter of 10 nm and a length of 5 μm in any weight ratio. Furthermore, in order to improve the weather resistance of the protective film, the polyester polyol is one of polyethylene adipate glycol and polycarbonate polyol or two of them in any weight ratio.
[0023] Furthermore, in order to improve the stability of the coating solution, the diisocyanate is one of hexamethylene diisocyanate and trimethylhexamethylene diisocyanate or a combination of the two in any weight ratio.
[0024] Furthermore, in order to improve the stability of the peeling force, the chain extender is one of 4,4'-methylenebis(2-methyl-6-ethylaniline) and 2,4-diamino-3,5-diethyltoluene or two of them in any weight ratio.
[0025] Furthermore, in order to improve the coating appearance, the solvent is one of ethyl acetate and butyl acetate or the two in any weight ratio.
[0026] Furthermore, in order to improve the stability of the peeling force, the catalyst is one of dibutyltin dilaurate and stannous octoate or a combination of the two in any weight ratio.
[0027] The blocked isocyanate of the present invention is selected from the following commercially available substances but is not limited thereto: one or any combination of B1358-100 (Evonik Degussa), BI358A (Evonik Degussa), BL3379 (Bayer, Germany), and HI100 (BASF, Germany) can be selected.
[0028] Another object of the present invention is to provide a method for preparing an adhesive for a UTG protective film, wherein the adhesive is prepared by the following steps: adding a proportion of polyester polyol, diisocyanate, chain extender and solvent to a reactor, reacting at 40°C-50°C for 20min-40min; adding a proportion of catalyst, heating to 70°C-90°C for 1h-3h; adding a proportion of antistatic agent, keeping at 70°C-90°C for 1h-2h, cooling to 40°C-50°C, adding a proportion of blocked isocyanate, and obtaining an adhesive for a UTG protective film. The method provided by the present invention prepares an adhesive with stable peeling force by controlling the addition order, heating time and temperature. The order of adding raw materials affects the polymer chain structure of the raw materials. The peeling force of adhesives with different polymer chain structures is quite different. In the present invention, the polymer structure is limited by limiting the order of adding materials; the heating time affects the degree of polymerization reaction. If the reaction time is short, the polymerization is easy to be incomplete, and there are unreacted small molecules in the system, which affects the peeling force of the adhesive. If the reaction time is long, polymerization reaction occurs between the isocyanate active groups to generate urea groups, which affects the peeling force; if the temperature is too high, violent polymerization is easy to occur, resulting in failure of the adhesive gel; if the reaction temperature is too low, the reaction speed is slow to rise to no reaction, making it difficult to prepare the adhesive.
[0029] The adhesive is applied in the present invention, mainly for UTG protective film. When applied, one side of the UTG protective film is coated with the adhesive for the UTG protective film, and a release film is attached to the adhesive layer. The polyester film of the present invention is a 50 μm optical grade polyester film. Preferably, the thickness of the adhesive layer of the present invention is 8 μm-12 μm, because the peeling force is controlled and the adhesion performance between the adhesive layer and the polyester film is increased.
[0030] The present invention is further described in detail below in conjunction with specific implementation modes, but the implementation of the present invention is not limited thereto. Example 1
[0031] (1) Add 10g of polyethylene adipate diol, 10g of polycarbonate polyol (CAS No.: 24937-06-2), 10g of 1,6-hexamethylene diisocyanate, 1g of 4,4'-methylenebis(2-methyl-6-ethylaniline), 1g of 2,4-diamino-3,5-diethyltoluene, and 40g of ethyl acetate into the reactor and react at 50°C for 20min; (2) Add 0.6 g of stannous octoate and heat to 85 °C for 2 h; (3) Add 0.83 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.21 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.21 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the reaction at 80 ° C for 2 h, cool to 50 ° C, add 2.5 g of B1358-100 (Evonik Degussa), 2.5 g of BI358A (Evonik Degussa), and 2.5 g of BL3379 (Bayer, Germany) to obtain an adhesive for UTG protective film.
[0032] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive surface to obtain a UTG protective film with a thickness of 12 μm. The performance evaluation results are listed in Table 1. Example 2
[0033] (1) Add 15g polycarbonate polyol (CAS No.: 24937-06-2), 4g 1,6-hexamethylene diisocyanate, 4g trimethylhexamethylene diisocyanate, 1g 2,4-diamino-3,5-diethyltoluene, 15g ethyl acetate, and 15g butyl acetate into the reactor and react at 45°C for 40min; (2) Add 0.15 g of dibutyltin dilaurate and 0.3 g of stannous octoate, and then raise the temperature to 90 °C for 1 h; (3) Add 0.25 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.15 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.1 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the reaction at 90 °C for 1 h, cool to 45 °C, add 4.5 g of BL3379 (Bayer, Germany), and 4 g of HI100 (BASF, Germany), to obtain an adhesive for UTG protective film.
[0034] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 10 μm. The evaluation results are listed in Table 1. Example 3
[0035] (1) Add 10 g of polyethylene adipate diol, 3 g of 1,6-hexamethylene diisocyanate, 8 g of trimethylhexamethylene diisocyanate, 0.5 g of 4,4'-methylenebis(2-methyl-6-ethylaniline), 1 g of 2,4-diamino-3,5-diethyltoluene, 20 g of ethyl acetate, and 15 g of butyl acetate into a reactor and react at 40°C for 30 min; (2) Add 0.4 g of dibutyltin dilaurate and heat to 75 °C for 1.5 h; (3) Add 1.43 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.17 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.4 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the mixture at 75 °C for 1.5 h, cool it to 42 °C, add 2.5 g of B1358-100 (Evonik Degussa), 2.5 g of BI358A (Evonik Degussa), 2.5 g of BL3379 (Bayer, Germany), and 2.5 g of HI100 (BASF, Germany), and obtain an adhesive for UTG protective film.
[0036] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 8 μm. The evaluation results are listed in Table 1. Example 4
[0037] (1) Add 5g of polyethylene adipate diol, 7.5g of polycarbonate polyol (CAS No.: 24937-06-2), 9g of 1,6-hexamethylene diisocyanate, 3g of 2,4-diamino-3,5-diethyltoluene, and 25g of ethyl acetate into the reactor and react at 47.5°C for 25min; (2) Add 0.1 g of dibutyltin dilaurate and 0.2 g of stannous octoate, and then raise the temperature to 70 °C and react for 2.5 h; (3) Add 0.75 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.1 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.15 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the reaction at 85 °C for 2 h, cool to 48 °C, add 2 g of BI358A (Evonik Degussa) and 3 g of HI100 (BASF, Germany), and obtain an adhesive for UTG protective film.
[0038] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film, the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 9 μm. The evaluation results are listed in Table 1. Example 5
[0039] (1) Add 17.5g polycarbonate polyol (CAS No.: 24937-06-2), 2g 1,6-hexamethylene diisocyanate, 10g trimethylhexamethylene diisocyanate, 1g 4,4'-methylenebis(2-methyl-6-ethylaniline), 1.5g 2,4-diamino-3,5-diethyltoluene, 5g ethyl acetate, and 15g butyl acetate into the reactor and react at 42.5°C for 35min; (2) Add 0.5 g of dibutyltin dilaurate and heat to 78 °C for 3 h; (3) Add 1.2 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.15 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.15 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the reaction at 70 ° C for 1.5 h, cool to 40 ° C, add 1.5 g of B1358-100 (Evonik Degussa), 2 g of BI358A (Evonik Degussa), and 3 g of HI100 (BASF, Germany) to obtain an adhesive for UTG protective film.
[0040] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 11 μm. The evaluation results are listed in Table 1. Comparative Example 1
[0041] (1) Add 10g of polyethylene adipate diol, 10g of polycarbonate polyol (CAS No.: 24937-06-2), 10g of 1,6-hexamethylene diisocyanate, 1g of 4,4'-methylenebis(2-methyl-6-ethylaniline), 1g of 2,4-diamino-3,5-diethyltoluene, and 40g of ethyl acetate into the reactor and react at 50°C for 20min; (2) Add 0.6 g of stannous octoate and heat to 85 °C for 2 h; (3) After the reaction was kept at 80°C for 2 h, the temperature was lowered to 50°C, and 2.5 g of B1358-100 (Evonik Degussa), 2.5 g of BI358A (Evonik Degussa), and 2.5 g of BL3379 (Bayer, Germany) were added to obtain an adhesive for the UTG protective film.
[0042] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 12 μm. The evaluation results are listed in Table 1. Comparative Example 2
[0043] (1) Add 15g polycarbonate polyol (CAS No.: 24937-06-2), 4g 1.6-hexamethylene diisocyanate, 4g trimethylhexamethylene diisocyanate, 1g 2,4-diamino-3,5-diethyltoluene, 15g ethyl acetate, and 15g butyl acetate into the reactor and react at 45°C for 40min; (2) Add 0.15 g of dibutyltin dilaurate and 0.3 g of stannous octoate, and then raise the temperature to 90 °C for 1 h; (3) Add 0.25 g of 86443-82-5 cationic quaternary ammonium salt surfactant, keep the reaction at 90 °C for 1 hour, then cool to 45 °C and add 4.5 g of BL3379 (Bayer, Germany) and 4 g of HI100 (BASF, Germany) to obtain an adhesive for UTG protective film.
[0044] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 10 μm. The evaluation results are listed in Table 1. Comparative Example 3
[0045] (1) Add 10 g of polyethylene adipate diol, 3 g of 1,6-hexamethylene diisocyanate, 8 g of trimethylhexamethylene diisocyanate, 0.5 g of 4,4'-methylenebis(2-methyl-6-ethylaniline), 1 g of 2,4-diamino-3,5-diethyltoluene, 20 g of ethyl acetate, and 15 g of butyl acetate into a reactor and react at 40°C for 30 min; (2) Add 0.4 g of dibutyltin dilaurate and heat to 75 °C for 1.5 h; (3) Add 0.17 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm) and 0.4 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm), keep the mixture at 75 °C for 1.5 h, cool it to 42 °C, add 2.5 g of B1358-100 (Evonik Degussa), 2.5 g of BI358A (Evonik Degussa), 2.5 g of BL3379 (Bayer, Germany), and 2.5 g of HI100 (BASF, Germany), and obtain an adhesive for UTG protective film.
[0046] The adhesive was coated on the surface of a 50 μm thick optical grade polyester film (PET), the polyester film was placed in an oven at 120°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain a UTG protective film with an adhesive layer thickness of 8 μm. The evaluation results are listed in Table 1.
[0047] The test methods for each performance in the table are as follows: (1) Transmittance and haze test Referring to the standard GB / T2410-2008, use a haze meter (model: "U3000"), tear off the release film, and measure the transmittance (T) and haze (H).
[0048] (2) Peel force test The protective film was cut into a size of 300×25 mm, the release film was torn off, and the protective film was attached to the surface of the polarizer. An electronic universal testing machine (model: AGS-X) was used to perform a peeling test at an angle of 180° and a tensile speed of 300 mm / min.
[0049] (3) Glue layer resistance test Cut the protective film into 12×12mm size, tear off the release film, and test the surface resistance of the film on a high resistance meter (model: SME-8310).
[0050] (4) High temperature and high humidity test Cut the protective film into 150×25mm size, tear off the release film, stick the protective film adhesive layer on the glass surface, put it into a programmable constant temperature and humidity test box, and observe whether the protective film has wrinkles, detachment, and bubbles on the glass surface after 500 hours at 85℃ and 85% humidity. If not, it is judged as qualified, if so, it is judged as unqualified.
[0051] Table 1 Performance data table
[0052] (1) Differences between Comparative Example 1 and Example 1: 0.83 g of 86443-82-5 cationic quaternary ammonium salt surfactant, 0.21 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm), and 0.21 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm) were added to Example 1, while no such surfactants were added to Comparative Example 1. Both the ionic quaternary ammonium salt surfactant and the multi-walled carbon nanotubes are substances that can reduce electrical resistance. After being added to the adhesive, the resistance of the adhesive layer can be effectively reduced. Therefore, the resistance of the adhesive layer of the protective film prepared in Example 1 is 1.93×10 9 Ω, the resistance of the protective film glue layer prepared in comparative example 1 is > 1×10 12 Ω.
[0053] (2) The difference between Comparative Example 2 and Example 2: In Example 2, 0.15 g of multi-walled carbon nanotubes (diameter 20 nm, length 1 μm) and 0.1 g of multi-walled carbon nanotubes (diameter 10 nm, length 5 μm) were added, while in Comparative Example 2, no multi-walled carbon nanotubes were added. Only cationic quaternary ammonium salt type surfactant was added to reduce the adhesive layer resistance of the protective film, but the effect was not very significant. The combination of multi-walled carbon nanotubes and cationic quaternary ammonium salt type surfactant can greatly reduce the adhesive layer resistance of the protective film.
[0054] (3) The difference between Comparative Example 3 and Example 3: In the example, multi-walled carbon nanotubes and cationic quaternary ammonium salt-type surfactants are used in combination, while in Comparative Example 3, only multi-walled carbon nanotubes are added. Multi-walled carbon nanotubes can effectively reduce the resistance of the adhesive layer of the protective film, but when used alone, they are prone to precipitation risks in the system. Cationic quaternary ammonium salt-type surfactants themselves are hydrophilic, and the surface of multi-walled carbon nanotubes contains carboxyl groups. The two have good compatibility and can improve the stability of the adhesive layer of the protective film.
[0055] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. An adhesive for a UTG protective film, characterized in that: The adhesive is polyester polyol, diisocyanate, chain extender, antistatic agent and blocked isocyanate, and a polymer free of silicon and fluorine is obtained in a solvent and catalyst environment, including the following substances in parts by weight: Polyester polyol 10-20 parts 8-12 parts of diisocyanate Chain extender 1-3 parts Solvent 20-40 parts Antistatic agent 0.5-2 parts Catalyst 0.3-0.6 parts 5-10 parts of blocked isocyanate.
2. The adhesive for UTG protective film according to claim 1, characterized in that: The antistatic agent is a mixture of ammonium salt and multi-walled carbon nanotubes, and the weight ratio of the ammonium salt to the multi-walled carbon nanotubes is 1:1-4:
1.
3. The adhesive for UTG protective film according to claim 2, characterized in that: The ammonium salt is a 86443-82-5 cationic quaternary ammonium salt surfactant; the multi-walled carbon nanotubes are two types of multi-walled carbon nanotubes with a diameter of 20 nm and a length of 1 μm and multi-walled carbon nanotubes with a diameter of 10 nm and a length of 5 μm in any weight ratio.
4. The adhesive for UTG protective film according to claim 1, characterized in that: The polyester polyol is one of polyethylene adipate glycol diol and polycarbonate polyol or two of them in any weight ratio; the diisocyanate is one of hexamethylene diisocyanate and trimethylhexamethylene diisocyanate or two of them in any weight ratio.
5. The adhesive for UTG protective film according to claim 1, characterized in that: The chain extender is one of 4,4'-methylenebis(2-methyl-6-ethylaniline) and 2,4-diamino-3,5-diethyltoluene or two of them in any weight ratio.
6. The adhesive for UTG protective film according to claim 1, characterized in that: The solvent is one of ethyl acetate and butyl acetate or two of them in any weight ratio; the catalyst is one of dibutyltin dilaurate and stannous octoate or two of them in any weight ratio.
7. A method for preparing an adhesive for a UTG protective film according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: a. Add the proportion of polyester polyol, diisocyanate, chain extender and solvent into the reactor and react at 40℃-50℃ for 20min-40min; b. Add a proportion of catalyst and heat to 70-90°C for 1-3 hours; c. Add a proportion of antistatic agent, keep the reaction at 70℃-90℃ for 1h-2h, cool to 40℃-50℃, add a proportion of blocked isocyanate, and obtain the adhesive for UTG protective film.
8. A UTG protective film, characterized in that: The UTG protective film is prepared by coating the adhesive for the UTG protective film as described in any one of claims 1 to 6 on the surface of a polyester film, and then laminating a layer of release film on the adhesive layer.
9. The UTG protective film according to claim 8, characterized in that: The polyester film is an optical grade polyester film of 50 μm, and the thickness of the adhesive layer is 8 μm-12 μm.
